Structural model of marital commitment based on differentiation and communication patterns in women: The mediating role of emotional intelligence - Fardad, Farah; Dokaneifard, Farideh; Mirhashemi, Malek (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to determine the structural pattern of marital commitment based on differentiation and communication patterns in women with a mediating role of emotional intelligence. Method: The research method was correlation and the statistical population was all married women who referred to counseling centers in Tehran in 1397. In this way, in the selection of counseling centers, simple random sampling was used by lot. For this purpose, the city of Tehran was first divided into five regions: north, south, east, west and center; Then, three counseling centers were randomly selected from each region by lottery and 300 women were selected based on Sample Power software. Then Adams and Jones (1997) Marital Commitment Questionnaire, Scorron and Friedlander (1998) Differentiation Questionnaire, Christensen & Sulawesi (1984) Communication Patterns Questionnaire and Bar-Anne (2002) Emotional Intelligence Questionnaire were completed and the data were analyzed using Smart Pls structural equations. Results: The results at the level of 99% confidence showed that the structural model can predict marital commitment based on differentiation and communication patterns mediated by emotional intelligence (β = 0.120) and has a good fit. The direct path of differentiation (β = 0.39) and communication patterns (β = 0.57), and emotional intelligence (β = 0.28) on significant marital commitment and the indirect path showed that differentiation and Communication patterns mediated by emotional intelligence have had a positive effect on marital commitment intensity. Conclusion: For the cohesion and creation of a desirable marital relationship, it is possible to improve couples' relationships by strengthening the emotional intelligence of each couple, the differentiation and type of communication patterns and the confrontation of their psychological elements.